Genomic changes in the biological control agent Cryptolaemus montrouzieri associated with introduction. (11th February 2019) - Li, Hao‐Sen; Heckel, Gerald; Huang, Yu‐Hao; Fan, Wei‐Jian; Ślipiński, Adam; Pang, Hong
Abstract: Biological control is the main purpose of intentionally introducing non‐native invertebrate species. The evolutionary changes that occur in the populations of the introduced biological control agents may determine the agent's efficiency and the environmental safety. Here, to explore the pattern and extent of potential genomic changes in the worldwide introduced predatory ladybird beetle Cryptolaemus montrouzieri, we used a reduced‐representation sequencing method to analyze the genome‐wide differentiation of the samples from two native and five introduced locations. Our analyses based on a total of 53, 032 single nucleotide polymorphism loci showed that beetles from the introduced locations in Asia and Europe exhibited significant reductions in genetic diversity and high differentiation compared with the samples from the native Australian range. Each introduced population belonged to a unique genetic cluster, while the beetles from two native locations were much more similar. These genomic patterns were also detected when the dataset was pruned for genomic outlier loci (52, 318 SNPs remaining), suggesting that random genetic drift was the main force shaping the genetic diversity and population structure of this biological control agent. Our results provide a genome‐wide characterization of polymorphisms in a biological control agent and reveal genomic differences that were influenced by the introduction history. These differences might complicate assessments of the efficiency of biological control and the invasion potential of this species but also indicate the feasibility of selective breeding.